Experiment on Effects of Dust, Heat and Cloud on a Solar Energy Generation in South-Western Part of Nigeria - Olalekan, Oyebola B. (Asian Journal of Electrical Sciences, 2018)
Currently, the world at large (including industries, companies, homes, financial institutions, transport, agricultural sector and educational sector) is highly dependent on energy or power for its operations or daily activities but the society has started questioning how modern life is being powered. The world has started to look for better alternatives. So, as the technology is advancing, a continuous and uninterruptible power supply system has come into place on the platform of research, discoveries and creativities. This brought about the innovation of an alternative power supply system known as solar system but yet, different questions like what makes up the solar system? Do environmental factors affect the working of a solar panel? And how do atmospheric conditions affect the efficiency of a solar panel? This work has been able to proffer solutions to these bothering questions from the society by carrying out experiments on the effects of dust, heat and cloudy day on the solar panel.